A) ac+bc+a+b=
b)x²-xy-2x+2y=
c)x²+xy+ax+ay=
d)x³+3x²+3x+9=
e)x²-xy-2xy+2y=
f)m²+mn-5m-5n=
g)a²-ab-3a+3b=
h)10ay-5by-2ax-bx=
i)6by-15bx-4ay+10ax=
j)5a²-5ax-7a+7x=
k)4x²-4xz-3x+3z=
l)ax²+bx-ax+a+b=
ł)ax²+bx²+ax-cx²+bx-cx=
m)ax²+bx²-bx-ax+cx²-cx=
n)5ax²-10ax-bx+2b-x+2=

1

Odpowiedzi

2010-03-09T13:57:31+01:00
A) ac+bc+a+b= a(c+1)+b(c+1)
b)x²-xy-2x+2y= x(x-y)-2(x-y)
c)x²+xy+ax+ay= x(x+y)+a(x+y)
d)x³+3x²+3x+9= x²(x+3)+3(x+3)
e)x²-xy-2xy+2y= x(x-y)-2(x-y)
f)m²+mn-5m-5n= m(m+n)-5(m+n)
g)a²-ab-3a+3b= a(a-b)-3(a-b)
h)10ay-5by-2ax-bx= 5y(2a-b)-x(2a+b)
i)6by-15bx-4ay+10ax= 3b(2y-5x)-2a(2y-5x)
j)5a²-5ax-7a+7x= 5a(a-x)-7(a-x)
k)4x²-4xz-3x+3z= 4x(x-z)-3(x-z)
l)ax²+bx-ax+a+b= ax(x-1)+b(x+1)+a
ł)ax²+bx²+ax-cx²+bx-cx= ax(x+1)+bx(x+1)-cx(x+1)
m)ax²+bx²-bx-ax+cx²-cx= ax(x-1)+bx(x-1)+cx(x-1)
n)5ax²-10ax-bx+2b-x+2= 5ax(x-2)-b(x-2)-(x-2)